Efektivitas Program Kali Bersih (PROKASIH) di Tukad Bindu Kelurahan Kesiman Kota Denpasar - I Putu Adi Permana Putra (Journal of Contemporary Public Administration, 2022)
The Clean River Program (PROKASIH) is a government policy in an effort to overcome pollution problems and maintain the preservation of environmental functions. Environmental problems, especially river pollution in Indonesia, are the reason for the need to maintain the function of waters to support development and improve human welfare. The purpose of this study is to assess the performance of policies to determine the effectiveness of the Clean River Program in overcoming the problem of river pollution. The research method used is a qualitative descriptive approach with data collection techniques through non-participatory observation, interviews, and documentation. The results of this study indicate that the implementation of the Clean River Program in Tukad Bindu, Kesiman Sub-district, Denpasar City is very effective. The effectiveness of the implementation of this program can be seen from the accuracy of policies in overcoming pollution problems in Tukad Bindu; target accuracy in program implementation; the accuracy of the implementation as proven through the synergy between the government, the private sector, and the local community; environmental accuracy as seen from the disposition and contribution of the community; accuracy of the process in complying with applicable rules and division of tasks; as well as the benefits obtained by the local community in the implementation of the Clean River Program as well as changes in behavior in maintaining and developing Tukad Bindu. The successful implementation of this program requires efforts to strengthen the institutional system in overcoming the problem of river pollution as well as optimizing community empowerment in realizing sustainable environmental management.